Islam, Cosmological Ethics, and Environmentalism: Reassessing Fazlun Khalid’s Thought on Ecology - Mukhlisin Saad; Umar Faruq; Muhibbin; Yusuph Dauda Gambari (TSAQAFAH, 2026)
This article seeks to reevaluate the intellectual contributions of Fazlun Khalid within the discourse of Islam and ecology. It is based on the argument that Khalid is not just a thinker but also an ecological practitioner, which distinguishes him from other scholars who typically engage with ecological issues through theological, philosophical, or Islamic jurisprudential lenses. Using textual and content analysis, this article argues that Khalid’s ecological view is rooted in his philosophical understanding of the universe. He not only criticizes the Western paradigm that places humans at the center of an existential relationship with nature, but also explicitly acknowledges the inherent value of nature itself, with the Qur’an as the basic framework for understanding this relationship. Khalid emphasizes that the Qur’an offers a holistic ecological vision, transcending the sacred-secular dichotomy, while emphasizing the interconnectedness of all creation. One of the fundamental aspects of its philosophical construction is the concept of fitra, which is described as the natural disposition that God instills in every human being. This concept shows that humans are inherently designed to interact with their environment in a balanced way.